Teachers’ old-fashioned classroom practices: A pitfall on the use of digital technology in mathematics teachings - Dwi Ratnasari; Kamirsyah Wahyu; Sofyan Mahfudy (Universitas Islam Negeri (UIN) Mataram, 2018)
[English]: The research aimed to analyze how novice teachers use digital technology and transform their practices from without-technology to with-technology mathematics teachings. Two upper secondary mathematics teachers were involved in this research. They were novice teachers in the use of digital technology in mathematics teachings. Classroom video recording and transcripts were the primary sources of data, meanwhile interview with the teachers and field notes are the supporting data. The teachings videos were categorized into some episodes, transcribed and analyzed following the phases of analyzing classroom video recordings and transcript by Cobb and Whitenack (1996). To capture the whole picture of the teachers’ practices, data analysis was referred to instrumental orchestration (Drijvers et al., 2010) and didactics tetrahedron unfolded (Hollebrands & Okumuş, 2018). In this research, we found that the observed teachers’ orchestrations are mostly non-technology orchestrations. The teachers have a different focus; one focuses only on mathematics and another focus on mathematics through the use of technology. The research concludes that old-fashioned classroom practices can be the pitfall for using digital technology in the mathematics classroom. Keywords: GeoGebra, Mathematics task, Digital technology, Pitfall, Teachers’ practices [Bahasa]: Penelitian ini bertujuan menganalisis bagaimana guru pemula menggunakan teknologi digital dalam kelas dan perubahan praktik pembelajaran setelah menggunakan teknologi. Dua guru matematika SMA menjadi subjek dalam penelitian. Subjek merupakan guru pemula terkait penggunaan teknologi digital dalam pembelajaran matematika. Data utama penelitian diperoleh melalui rekaman video pembelajaran. Hasil wawancara dengan guru dan catatan lapangan digunakan sebagai data pendukung. Video pembelajaran dikelompokkan menjadi beberapa episode, dibuat transkrip dan dianalisis berdasarkan langkah-langkah analisis rekaman video dan transkrip pembelajaran oleh Cobb and Whitenack (1996). Untuk memperoleh gambaran menyeluruh praktik guru, analisis data merujuk pada kerangka orkestra instrumental (Drijvers et al, 2010) dan segiempat didaktik terbuka (Hollebrands & Okumuş, 2018). Penelitian ini menemukan bahwa sebagian besar orkestra guru dalam pembelajaran masih bercirikan pembelajaran tanpa teknologi. Dua guru dalam penelitian ini memiliki fokus yang berbeda dalam pembelajaran yaitu fokus hanya pada matematika dan fokus pada matematika melalui penggunaan teknologi. Hasil penelitian tersebut menunjukan bahwa praktik rutin guru tanpa teknologi bisa menjadi hambatan dalam pembelajaran berbasis teknologi. Kata kunci: GeoGebra, Tugas matematika, Teknologi digital, Hambatan, Praktik guru